Effects of Wheat Varieties on Bacterial Community and Volatile Flavor Compounds in Nongxiangxing Daqu - Xiaoge HOU; Junpeng FAN; Fuli GUO; Zheng LI; Xin HU; Ming HUI; Ruifang LI; Xiyu SUN; Chunmei PAN (Shipin gongye ke-ji)
Wheat was the main raw material for producing daqu, but the diversity in the characteristics of wheat varieties influenced daqu production. To investigate the effects of wheat varieties on the bacterial community and the flavor-related metabolites in Nongxiangxing daqu, the main properties and components of wheat were determined by national standard methods, 16S rDNA amplicon high-throughput sequencing technology and headspace solid-phase microextraction gas chromatography/mass spectrometry (HS-SPME-GC/MS) technology were applied to analyze the bacterial community and volatile compounds in Nongxiangxing daqu derived from different wheat varieties, respectively. The correlation between wheat quality indices and the dominant bacterial genera was visualized by constructing a Spearman rank correlation-based network diagram. According to the crude protein content, five wheat varieties were classified into the following four categories: high-gluten, medium-high-gluten, medium-gluten, and low-gluten wheat. A total of 83 volatile compounds were detected in Nongxiangxing daqu, of which 43 were differentially abundant compounds. Additionally, hexanol, ethyl 2-methylbutyrate, ethyl isovalerate, and tetramethylpyrazine were identified as potentially useful volatile compound markers of Nongxiangxing daqu produced from high-gluten wheat, whereas butenal might be used as a marker of Nongxiangxing daqu derived from medium-gluten wheat. The medium-gluten and low-gluten wheat varieties produced the Nongxiangxing daqu with the highest total aerobic bacteria and acid-producing bacteria contents, respectively, with Kroppenstedtia, Thermoactinomyces, Leucobacter, Weissella, and Bacillus identified as the predominant bacterial genera. Weissella and Thermoactinomyces bacterial species were relatively abundant in the Nongxiangxing daqu produced from medium-gluten and medium-high-gluten wheat varieties, but not in the Nongxiangxing daqu derived from the high-gluten wheat. Furthermore, the four most abundant bacterial genera were significantly related to the differentially abundant volatile compounds. Moreover, they were affected by the crude protein or wet gluten contents, the crude starch content, and the powder rate of wheat grains. The study results provide a theoretical basis for breeding ideal wheat varieties for the production of daqu, including Nongxiangxing daqu.